2004
DOI: 10.1039/b402995j
|View full text |Cite
|
Sign up to set email alerts
|

Indoor air quality during renovation actions: a case study

Abstract: A temporary renovation activity releases considerably high concentrations of particulate matter, viable and non-viable, into air. These pollutants are a potential contributor to unacceptable indoor air quality (IAQ). Particulate matter and its constituents lead, sulfate, nitrate, chloride, ammonium and fungi as well as fungal spores in air were evaluated in a building during renovation action. Suspended dust was recorded at a mean value of 6.1 mg m(-3) which exceeded the Egyptian limit values for indoor air (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…Distinct from Cryptococcus , however, Aspergillus can produce small asexual spores, called conidia, which are 2–3 μm in diameter. The dispersal of A. fumigatus produces conidia that are hydrophobic and can spread and sustain for a much longer time in the air, making it a highly virulent fungus [ 53 , 54 , 55 ]. In healthy individuals, epithelial cells in the airway and alveolar macrophages efficiently eliminate inhaled conidia, but resident conidia can evade mucocilliary clearance and lodge in the alveoli deep in the lungs, germinating into short hyphae in less than 6 h [ 56 ].…”
Section: Fungal Infectionmentioning
confidence: 99%
“…Distinct from Cryptococcus , however, Aspergillus can produce small asexual spores, called conidia, which are 2–3 μm in diameter. The dispersal of A. fumigatus produces conidia that are hydrophobic and can spread and sustain for a much longer time in the air, making it a highly virulent fungus [ 53 , 54 , 55 ]. In healthy individuals, epithelial cells in the airway and alveolar macrophages efficiently eliminate inhaled conidia, but resident conidia can evade mucocilliary clearance and lodge in the alveoli deep in the lungs, germinating into short hyphae in less than 6 h [ 56 ].…”
Section: Fungal Infectionmentioning
confidence: 99%
“…The renovation and remodeling of buildings are usually the main sources of indoor air pollutants (Lioy et al 1992;Turner 1998;Yiin et al 2004;Bogovski et al 2007;Young et al 2008;Hasegawa et al 2009), with dust, heavy metals, fibers, gases, bio-aerosols, volatile and semi-volatile organic compounds the major air pollutants generated by renovation actions (Hameed et al 2004). Exposure to lead, for example, can occur when leadbased paints are improperly removed from surfaces through sanding, dry scraping, flame burning and demolition (Sen et al 2002;Farfel et al 2003;Bernstein et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that household renovation releases particulate matter, volatile organic compound (VOCs), lead, sulfate, nitrate, chloride, ammonium, and fungi that deteriorate indoor air quality, damage the immune system and result in bad health outcomes 14‐17 . In their study of Malaysia, Norbäck et al 18 proposed that formaldehyde and BTEX in indoor air were risk factors for fatigue, headache, ocular, and throat symptoms in high school students.…”
Section: Introductionmentioning
confidence: 99%